2022
DOI: 10.1111/bdi.13207
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women with bipolar disorder who have a history of childhood maltreatment: Intergenerational effects of trauma on fetal neurodevelopment and birth outcomes

Abstract: Objectives: Intergenerational transmission of trauma occurs when the effects of childhood maltreatment (CM) influence the next generation's development and health; prenatal programming via maternal mood symptoms is a potential pathway. CM is a risk factor for bipolar disorder which is present in 1.8% of pregnant women. Mood symptoms are likely to increase during pregnancy, particularly for those with a history of CM. We examined whether there was evidence for intergenerational transmission of trauma in utero i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Babineau et al found that childhood maltreatment experienced by pregnant women with bipolar disorder can in uence the development and health of the next generation. They also found that maternal mood may be a transmission pathway (53). It seems that childhood trauma can exert both prenatal and postnatal effects on development and health.…”
Section: Discussionmentioning
confidence: 99%
“…Babineau et al found that childhood maltreatment experienced by pregnant women with bipolar disorder can in uence the development and health of the next generation. They also found that maternal mood may be a transmission pathway (53). It seems that childhood trauma can exert both prenatal and postnatal effects on development and health.…”
Section: Discussionmentioning
confidence: 99%
“…These changes leave the mother more susceptible to infection and illness during pregnancy and may also represent mechanisms by which long‐term maternal mental and physical health is affected (Coussons‐Read, 2013). Prenatal adversity has been linked to mood disorders in the postnatal period, which may affect maternal caregiving behavior and lifestyle, and in turn exert adverse effects on offspring (Babineau et al., 2022).…”
Section: Introductionmentioning
confidence: 99%